BRCA testing and management of BRCA-mutated early-stage breast cancer: a comprehensive statement by expert group from GCC region - Al-Shamsi, Humaid O.; Alwbari, Ahmed; Azribi, Fathi; Calaud, Francois; Thuruthel, Sanjay; Tirmazy, Syed Hammad Hassan; Kullab, Sharif; Ostomane, Sonia; Abulkhair, Omalkhair (Frontiers in Oncology, 2024)
BReast CAncer (BRCA)1 and BRCA2 gene pathogenic variants account for most hereditary breast cancers (BC). Identification of BRCA mutations can significantly influence both prognosis and treatment outcomes. Furthermore, it enables the identification of individuals who are at heightened risk of developing BC due to inherited genetic mutations. Many developing countries rely on western guidelines for BRCA testing and BC management; however, there exist wide disparities in the prevalence of risk factors, availability of medical resources, and practice patterns. Guidelines tailored to specific regions can help mitigate healthcare variations, promote consistency in treatment, and aid healthcare providers in identifying effective therapies for improving patient outcomes. Hence, oncologists from the Gulf Cooperation Council (GCC) congregated virtually in March 2023 and reviewed existing data on the epidemiology of BC, BRCA mutations, practices and challenges associated with BRCA testing and management of BRCA mutated early-stage BC in the GCC region. They also provided insights on the real-world diagnostic and treatment practices and challenges in the GCC region in the BRCA-mutated early-stage BC domain and suggested some variations to international guidelines to aid their uptake in this region.